Ultrasound Reversibly Disaggregates Fibrin Fibers - Braaten, Julie V; Goss, Rachel A; Francis, Charles W (Thrombosis and Haemostasis, 1997)
Ultrasound accelerates fibrinolysis in vitro and in vivo, primarily through non-thermal mechanisms including cavitation. We have previously observed that ultrasound reversibly increases flow through fibrin gels, a property primarily determined by the structure of the fibrin matrix. Therefore, the effect of ultrasound on the ultrastructure of fibrin gels was examined using scanning electron microscopy. Non-cross- linked fibrin gels were fixed and prepared for microscopy before, during and after exposure to 1 MHz ultrasound, and quantitative analysis of fiber population density and diameter was performed. Gels exposed and fixed in the presence of ultrasound exhibited an increase in density of 65 ± 26% (mean ± SD) at 4 W/cm2 (p <0.000001) accompanied by a decrease in fiber diameter of 27 ± 9% (p <0.000001). Gels fixed 15 min following ultrasound exposure showed no significant change in either density or diameter compared to unexposed gels, indicating that the ultrasound-induced change in fiber structure was reversible. Factor XIII-crosslinked fibrin gels exhibited no change in population density or diameter when exposed to ultrasound. These results indicate that ultrasound exposure causes reversible disaggregation of uncrosslinked fibrin fibers into smaller fibers, an effect that may alter flow resistance and create additional binding sites for fibrinolytic components, improving fibrinolytic efficacy.